2021
DOI: 10.3390/su13168995
|View full text |Cite
|
Sign up to set email alerts
|

Models of Sports Management in Fitness Centres. Influence of Sex, Age and Sport Frequency. Linear Models vs. Qualitative Comparative Analysis

Abstract: Knowing the perceptions of users of sports services has always been an object of analysis within sports management. This paper attempts to analyse what influences the satisfaction and future intentions of fitness centre customers, beyond management variables, by using two different methodologies. A sample of 389 users of a private sports centre was used. Both linear relationships between variables and the combination of sets were analysed using fuzzy set Qualitative Comparative Analysis fsQCA. It is concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Perceived value, on the other hand, is a much broader concept defined as "the consumer's evaluation of the usefulness of a product based on the perception of what is given and received" (Woodruff, 1997, p. 142), or "the heart of modern approximation to marketing" (Nilson, 1992, p. 32). Attempts to understand the value consumers place on the fitness industry have resulted in numerous studies of perceived quality and perceived value (Alguacil et al, 2019;Eskiler & Altunışık, 2021;García-Pascual et al, 2021;Theodorakis et al, 2014). Perceived quality has been identified as an important antecedent of perceived value.…”
Section: Relationship Between Perceived Quality and Perceived Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Perceived value, on the other hand, is a much broader concept defined as "the consumer's evaluation of the usefulness of a product based on the perception of what is given and received" (Woodruff, 1997, p. 142), or "the heart of modern approximation to marketing" (Nilson, 1992, p. 32). Attempts to understand the value consumers place on the fitness industry have resulted in numerous studies of perceived quality and perceived value (Alguacil et al, 2019;Eskiler & Altunışık, 2021;García-Pascual et al, 2021;Theodorakis et al, 2014). Perceived quality has been identified as an important antecedent of perceived value.…”
Section: Relationship Between Perceived Quality and Perceived Valuementioning
confidence: 99%
“…The relationship between perceived quality and perceived value in fitness services has been discussed in different studies (Chiu et al, 2017;García-Fernández et al, 2018Yu et al, 2014). In the fitness industry literature, perceived quality and perceived value are seen as the antecedent variables before loyalty (García-Pascual et al, 2021). Perceived value has been seen as a key factor in the success of businesses.…”
Section: Relationship Between Perceived Quality and Perceived Valuementioning
confidence: 99%
“…Recent studies have shown the impact of the quality of the processes linked to the operating methods on the one hand, and the quality of the results on the other, on the creation of value, overall satisfaction, and the conditions for loyalty. They have focused on fitness centres in Malaysia [30] and Spain [31,32] and on aquatic facilities in Australia [33,34] and Hong Kong [24]. All these studies used indicators related to the operational phase within the structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have shown that children with access to nearby parks and recreational facilities are more active than other children [26,27]. Some scholars have conducted research from the perspective of gender [11,[28][29][30]. Due to differences in social status and family responsibilities, women are often more restricted in their fitness activities [31].…”
Section: Literature Reviewmentioning
confidence: 99%